EDUCATION OF POLITICAL CULTURE FOR FUTURE OFFICERS OF THE ARMED FORCES OF UKRAINE - IMPERATIVE TIME - Hryhoriy Vasyanovych (Vasyl Stefanyk Precarpathian National University, 2018)
The article substantiates the idea of raising political culture of future officers of Ukrainian Armed Forces. It characterizes main symptom-complexes of political culture qualities including political competence; political identity; political activeness and initiative; political positioning; it defines ways of implementation political culture of a future officer on a practical level. Key words: political culture of a future officer of Ukrainian Armed Forces, cadets of higher military institutions, political competence; political identity; political activeness and initiative; political positioning of personal political culture of a future officer.